1989
DOI: 10.1128/iai.57.10.3159-3164.1989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Salmonella paratyphi C Vi polysaccharide

Abstract: The Vi capsular polysaccharide (Vi) is both a virulence factor and a protective antigen of SalmoneUa typhi; its pathogenic role for SalmoneUa paratyphi C is less well understood. We found no differences between the antigenic and immunogenic properties and the structure of the Vi from representative strains of S. paratyphi C, S. typhi, and Citrobacterfreundii. There were, however, differences in both the amount produced per cell and the degree of association with the cell among the Vi from the three species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…(v) Strains of S. typhi lacking Vi-antigen genes. In our sample of 334 isolates of S. typhi, 6 isolates of Tp 1 and 4 isolates of Tp 2 were phenotypically Vi negative. When probed for the viall region (53), four Tp 1 isolates and three Tp 2 isolates were positive, but DNA from the other two isolates of Tp 1 and from one isolate of Tp 2 failed to hybridize with the probe, thus demonstrating that a small proportion of S. typhi strains do not carry the Vi-antigen genes.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…(v) Strains of S. typhi lacking Vi-antigen genes. In our sample of 334 isolates of S. typhi, 6 isolates of Tp 1 and 4 isolates of Tp 2 were phenotypically Vi negative. When probed for the viall region (53), four Tp 1 isolates and three Tp 2 isolates were positive, but DNA from the other two isolates of Tp 1 and from one isolate of Tp 2 failed to hybridize with the probe, thus demonstrating that a small proportion of S. typhi strains do not carry the Vi-antigen genes.…”
Section: Resultsmentioning
confidence: 60%
“…In the case of S. paratyphi C, we have demonstrated that the frequent failure of strains in laboratory culture to produce the Vi antigen is, with rare exception (1 of 35 phenotypically Vi-negative isolates probed), not attributable to an absence of the viaB gene region (61). Daniels et al (6) found that strains of S. paratyphi C rapidly lose Vi expression when passed on laboratory medium. In view of this finding and the observation that 67 of 78 isolates recovered in the course of an epidemic of enteric fever in South Africa and stored freeze-dried were Vi positive, Daniels et al (6) suggested that most strains of S. paratyphi C have Vi in the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data showed that expression of the Vi-antigen blocked O-antigen agglutination in both S. Typhi and S. Typhimurium. It is relevant to mention in this context, that although the viaB locus is present in S. enterica serotype Paratyphi C, expression of the Vi-antigen does not interfere with O-antigen agglutination in this serotype (Daniels et al, 1989).…”
Section: Expression Of the Vi-capsule In S Typhimurium Prevents O-anmentioning
confidence: 99%
“…Salmonella Paratyphi A and B do not produce Vi polysaccharide. S. Paratyphi C, expresses Vi, but it is a very rare cause of enteric fever [53] [27]. These findings are intriguing, although information about serotypes other than S. Typhi are quite limited and require larger studies targeted toward these serotypes to draw conclusions.…”
Section: Discussionmentioning
confidence: 99%